2008
DOI: 10.1038/oby.2008.298
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study on the Effect of Shift Work on Weight Gain in Male Japanese Workers

Abstract: objective: This study compared the effect of alternating shift work and day work on weight gain in Japanese male workers. Methods and Procedures: A longitudinal cohort study was conducted in day workers (n = 4,328) and alternating shift workers (n = 2,926) of a steel company who received annual health checkups over a 14-year period between 1991 and 2005. The association between the type of job schedule and weight gain was investigated using multivariate pooled logistic regression analyses. The endpoints in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
170
0
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(194 citation statements)
references
References 45 publications
13
170
0
11
Order By: Relevance
“…Antunes et al investigated the effect of shift work on BMI and WHR concluded the difference was significant in waist circumference and BMI of shift workers than day works, which was consistent with the results of this study (25). The results of this study showed that with increasing age and work experience, rapid changes were observed in BMI and WHR, which was in agreement with the results of the study by Suwazono et al (26). Moreover, the results of the study by Gholami Fesharaki et al showed that with increasing age and work experience, the rates of obesity and BMI also increased that confirms the results of this study (27).…”
Section: Discussionsupporting
confidence: 83%
“…Antunes et al investigated the effect of shift work on BMI and WHR concluded the difference was significant in waist circumference and BMI of shift workers than day works, which was consistent with the results of this study (25). The results of this study showed that with increasing age and work experience, rapid changes were observed in BMI and WHR, which was in agreement with the results of the study by Suwazono et al (26). Moreover, the results of the study by Gholami Fesharaki et al showed that with increasing age and work experience, the rates of obesity and BMI also increased that confirms the results of this study (27).…”
Section: Discussionsupporting
confidence: 83%
“…Long-term experiments in populations showing disrupted sleep/wake patterns are thus necessary to probe these findings further, but a longitudinal study in a nurses cohort of night-shift work has found that exposure to night work can lead to weight gain and obesity (29). More recently, it was found that alternating shift work is an independent risk factor for the development of obesity in a longitudinal (14-y) large cohort of Japanese male shift workers (30). Thus, the ability to model some of these effects in animals may provide methods to intervene and either reverse or protect an individual from the negative physiological ramifications of long-term shift work.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have utility in avoiding some confounding or effect modification due to sex, work environment and shift patterns, but also generate data that might not be applicable to the general population. [1,2] Large population based studies of the general workforce that adjust for multiple lifestyle and workrelated confounding factors are required to address these challenges of studying the effects of shiftwork on health.…”
Section: Discussionmentioning
confidence: 99%
“…Keywords circadian depression diabetes neuroticism nightshift obesity shiftwork well being BACKGROUND Shiftwork is associated with detrimental effects on health and wellbeing, including increased risk of diabetes [1][2][3][4][5] and sleep problems, [6][7][8] higher body mass index (BMI) [1,[9][10][11][12], and increased signs of anxiety and depression. [8,13,14] Shiftworkers were once predominantly male, manufacturing sector workers, but this is no longer the case; a recent government survey reported that security services, transport and communications industries were the most common occupation of shiftworkers in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%